Microbial diversity of bacterial cellulose starter culture revealed by 16S rRNA gene amplicon sequencing - ALEYDA NUR HALIZAH WAHYUDI; TRI ARDYATI; ARIE SRIHARDYASTUTIE (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Wahyudi ANH, Ardyati T, Srihardyastutie A. 2026. Microbial diversity of bacterial cellulose starter culture revealed by 16S rRNA gene amplicon sequencing. Biodiversitas 27 (6): d270614. https://doi.org/10.13057/biodiv/d270614. Bacterial Cellulose (BC) is a biopolymer produced through microbial fermentation and widely applied in food, biomedical, and industrial fields. The performance of BC production is strongly influenced by the microbial composition of the starter culture. However, detailed information on the bacterial community structure of BC starter remains limited due to the constraints of culture-dependent methods. The aim of this research is to characterize the bacterial diversity and community composition of a BC starter culture using 16S rRNA gene amplicon sequencing and to complement the molecular data with culture-based enumeration. The starter culture was rejuvenated in coconut water medium and incubated at 30°C for 14 days. Cultivable bacteria capable of growing on Hestrin-Schramm medium were quantified using total plate count, yielding a population of (1.91±0.16) × 10⁹ CFU/mL. Amplicon sequencing analysis revealed a bacterial community with high richness but low evenness, characterized by strong taxonomic dominance. A total of 349 observed taxa were detected, with Firmicutes representing the dominant phylum (94.6%). At the genus level, Lentilactobacillus accounted for 86.9% of the relative abundance, while Lentilactobacillus parafarraginis was identified as the most abundant species (87%). These findings indicate that the BC starter culture analyzed in this research was dominated by lactic acid bacteria, particularly Lentilactobacillus. This pattern may suggest a possible role of Lentilactobacillus spp. in shaping the fermentation environment. The results provide a descriptive baseline for understanding the microbial ecology of BC starter culture to clarify the ecological significance of the dominant taxa.